Specific c-Jun N-Terminal Kinase Inhibitor, JNK-IN-8 Suppresses Mesenchymal Profile of PTX-Resistant MCF-7 Cells through Modulating PI3K/Akt, MAPK and Wnt Signaling Pathways - KILBAŞ, PELİN ÖZFİLİZ; Sönmez, Özlem; Uysal-Onganer, Pınar; Çoker Gürkan, Ajda; YERLİKAYA, PINAR OBAKAN; ARISAN, ELİF DAMLA (MDPI, 2020)
Paclitaxel (PTX) is a widely used chemotherapeutic agent in the treatment of breast cancer, and resistance to PTX is a common failure of breast cancer therapy. Therefore, understanding the effective molecular targets in PTX-resistance gains importance in identifying novel strategies in successful breast cancer therapy approaches. The aim of the study was to investigate the functional role of PTX resistance on MCF-7 cell survival and proliferation related to PI3K/Akt and MAPK pathways. The generated PTX-resistant (PTX-res) MCF-7 cells showed enhanced cell survival, proliferation, and colony formation potential with decreased cell death compared to wt MCF-7 cells. PTX-res MCF-7 cells exhibited increased motility profile with EMT, PI3K/Akt, and MAPK pathway induction. According to the significant SAPK/JNK activation in PTX-res MCF-7 cells, specific c-Jun N-terminal kinase inhibitor, JNK-IN-8 is shown to suppress the migration potential of cells. Treatment of JNK inhibitor suppressed the p38 and SAPK/JNK and Vimentin expression. However, the JNK inhibitor further downregulated Wnt signaling members in PTX-res MCF-7 cells. Therefore, the JNK inhibitor JNK-IN-8 might be used as a potential therapy model to reverse PTX-resistance related to Wnt signaling.
Keywords: Paclitaxel; JNK; WNT; Drug Resistance; Breast Cancer